24-Month-Old Infants’ Interpretations of Novel Verbs and Nouns in Dynamic Scenes - Waxman, Sandra R. (2009)
The current experiments address several concerns, both empirical and theoretical in nature, that have surfaced within the verb-learning literature. They begin to reconcile what, until now, has been a large and largely unexplained gap between infants’ well-documented ability to acquire verbs in the natural course of their lives and their rather surprising failures to do so in many laboratory-based tasks. We presented 24-month-old infants with dynamic scenes (e.g., a man waving a balloon), and asked a) whether infants could construe these scenes flexibly, noticing the consistent action (e.g., waving) as well as the consistent object (e.g., the balloon) and b) whether their construals of the scenes were influenced by the grammatical form of a novel word used to describe them (verb or noun). Infants successfully mapped novel verbs to event categories (e.g., waving events) and novel nouns to object categories (e.g., balloons). Moreover, infants’ representations were sufficiently abstract to permit them to extend novel verbs and nouns appropriately beyond the precise scenes on which they had been taught.